PENINGKATAN KETERAMPILAN BERPIKIR KREATIF MELALUI MODEL INKUIRI TERBIMBING BERORIENTASI ELEMEN PEDAGOGIS ESD (EDUCATION FOR SUSTAINABLE DEVELOPMENT) PADA SISWA SMP - Nabila Nuzul Nawafila, Sherly; Rosdiana, Laily (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to examine students’ creative thinking skills, the implementation fidelity of the learning process, and students’ responses following the application of a guided inquiry model oriented toward the pedagogical elements of Education for Sustainable Development (ESD) in renewable energy learning. This study employed a pre-experimental method with a one-group pretest–posttest design. The participants consisted of 30 ninth-grade students (class IX-D) at UPT SMPN 18 Gresik in the 2025/2026 academic year. The improvement in students’ creative thinking skills was indicated by an N-Gain score of 0.54, which falls into the moderate category. The normality test results (pretest: p = 0.001; posttest: p = 0.013) revealed that the data were not normally distributed. Furthermore, the Wilcoxon signed-rank test yielded a significance value of p = 0.000, indicating a statistically significant difference in students’ creative thinking skills before and after the intervention. The calculated effect size of 0.877 suggests a very strong practical impact of the implemented model. In addition, the implementation of the learning process achieved a mode score of 4, categorized as very good. Students’ responses reached 85%, indicating a highly positive perception of the learning experience. These findings demonstrate that the ESD-oriented guided inquiry model is effective in enhancing junior high school students’ creative thinking skills in the context of renewable energy learning